Optimalisasi Manajemen Pemasaran Usaha Tour dan Travel PT. Nur Haramain Mulia - ali, muhammad zakaria; Putriani, Erin Nur; Wardi, Fithriah (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
Nur Haramain Mulia is a company that is relatively fast growing by having branches in the Sidoarjo, Madura, Lumajang and Aceh areas. This is the basis for the researcher to find out the optimization of marketing management of the Tour and Travel business of PT. Nur Haramain Mulia. In this case, the researcher will focus on the Umrah business which is in demand by many pilgrims because of the long waiting list for Hajj. The research method used in this study is the Qualitative Descriptive Method. Then the researcher also used the SWOT Analysis method. For strengths and weaknesses, they come from the internal environment while opportunities and obstacles come from the external environment (Suriano, 2022). The following is an analysis of the Swot of PT Nur Haramain Mulia 1. Strengths such as: Conducting effective marketing and promotion through various media, such as websites, social media, advertisements, and exhibitions, to reach a wide target market following PT Nur Haramain Mulia IG Nur Haramain Mulia social media with 2374 followers. Fb Nur. Haramain. Mulia has 4900 followers. YouTube Nur Haramain Mulia with 1031 followers. TikTok Nur Haramain Mulia with 2894 followers and 30.6 thousand likes. 2. Weakness: There is a change in the price from what is stated in the brochure. 3. Opportunity: PT Nur Haramain Mulia has become the first Umrah bureau in Probolinggo Regency that has an official permit from the Ministry of Religious Affairs. This makes PT Nur Haramain Mulia better known by the community, especially the Probolinggo area.4. Threat: The emergence of a new Umrah bureau with an attractive pricing and service strategy.